Antioxidant and antiproliferative potentials of phenolic-rich extracts from biotransformed grape pomace in colorectal Cancer - Katarina Mišković Špoljarić; Gordana Šelo; Ena Pešut; Josipa Martinović; Mirela Planinić; Marina Tišma; Ana Bucić-Kojić (BMC, 2023)
Abstract Background Colorectal carcinoma is one of the most commonly diagnosed malignancies worldwide. Consumption of dietary supplements and nutraceuticals such as phenolic compounds may help combat colorectal carcinoma. The effect of two phenolic-rich extracts prepared from biotransformed grape pomace on the antioxidant properties and antiproliferative activity against two colorectal cancer cell lines (Caco-2 and SW620) were investigated. Methods A 15-day solid-state fermentation with the white-rot fungi Phanerochaete chrysosporium and Trametes gibbosa was used to biotransform grape pomace. Solid-liquid extraction was then performed to extract bioactive compounds. The extract was analyzed for the determination of phenolic compounds by ultra-high performance liquid chromatography and in vitro assays of biological activities (antioxidant activity, antiproliferative activity, cell cycle analysis). Results The 4 days of solid-state fermentation proved to be the optimal period to obtain the maximum yield of phenolic compounds. The tested extracts showed significant antioxidant and antiproliferative activities. Grape pomace treated with P. chrysosporium and T. gibbosa reduced cancer cell growth by more than 60% at concentrations (solid/liquid ratio) of 1.75 mg/mL and of 2.5 mg/mL, respectively. The cell cycle perturbations induced by the grape pomace extracts resulted in a significant increase in the number of cells in the S (9.8%) and G2/M (6.8%) phases of SW620 exposed to T. gibbosa after 48 hours, while P. chrysosporium increased the percentage of cells in the G1 phase by 7.7%. The effect of grape pomace extracts on Caco-2 was less pronounced. Conclusions The obtained results suggest the presence of bioactive compounds in biotransformed grape pomace as a residue from winemaking, which could be used to prevent colon cancer.